2021
DOI: 10.1080/19768354.2021.1995486
|View full text |Cite
|
Sign up to set email alerts
|

Mirodenafil ameliorates skin fibrosis in bleomycin-induced mouse model of systemic sclerosis

Abstract: Systemic sclerosis (SSc) is a chronic autoimmune disease characterized by fibrosis of the skin and internal organs. Despite the recent advances in the pathogenesis and treatment of SSc, effective therapies for fibrosis caused by SSc have not yet been established. In this study, we investigated the potential role of mirodenafil, a potent phosphodiesterase 5 (PDE5) inhibitor, in the treatment of fibrosis in SSc. We used a bleomycin (BLM)-induced SSc mouse model to mimic the typical features of fibrosis in human … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…Evidence showed that PDE inhibitors could reduce skin fibrosis as well. Mirodenafil, a potent PDE5 inhibitor, ameliorated dermal fibrosis in the BLM-induced mice and downregulated the expression of profibrotic genes and collagen in fibroblasts, possibly by suppressing TGF-β/Smad signalling pathway ( Roh et al, 2021 ). Sildenafil, a well-known PDE5 inhibitor, prevents ROS-induced instability in human dermal fibroblasts isolated by SSc patients ( Di Luigi et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Evidence showed that PDE inhibitors could reduce skin fibrosis as well. Mirodenafil, a potent PDE5 inhibitor, ameliorated dermal fibrosis in the BLM-induced mice and downregulated the expression of profibrotic genes and collagen in fibroblasts, possibly by suppressing TGF-β/Smad signalling pathway ( Roh et al, 2021 ). Sildenafil, a well-known PDE5 inhibitor, prevents ROS-induced instability in human dermal fibroblasts isolated by SSc patients ( Di Luigi et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, it has been reported that the number of patients with IPF has increased over time (Liu et al 2017 ). Pulmonary fibrosis (PF) is characterized by abnormal accumulation of the extracellular matrix (ECM), alveolar epithelial cell damage, vascular remodeling, and irreversible lung damage (Todd et al 2012 ; Liu et al 2017 ; Roh et al 2021 ). Previous studies have focused on inflammation as an important cause of pathogenesis; however, myofibroblasts, which are significant mediators of fibrosis known to produce ECM proteins, have been receiving more attention in recent years (Todd et al 2012 ; Liu et al 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…As normal histopathological tests often involve general staining such as hematoxylin–eosin (H&E) staining (No et al 2021 ; Roh et al 2021 ), the development of a fluorescence staining equivalent to H&E staining is important. Eosin labels cytosol in red and exhibits red fluorescence via the conventional rhodamine filter setup of a fluorescence microscope.…”
Section: Introductionmentioning
confidence: 99%